Bispidine dioxotetraaza macrocycles: a new class of bispidines for 64Cu PET imaging - Comba, Peter; Rudolf, Henning (Inorganic chemistry, 2014)
The three new dioxo-tetraazamacrocyclic ligands with a fused, very rigid bispidine (3,7-diazabicyclo[3.3.1]nonane) group connecting the two tertiary amine donors, and ethyl, propyl, or benzene groups connecting the two amide donors are highly preorganized and lead to very stable, uncharged CuII complexes. Solution spectroscopy and solid state structures indicate that these are square pyramidal with a solvent molecule occupying the apical position. Cyclic voltammetry defines a reversible CuIII/II couple and a strongly negative irreversible CuII/I couple (ca. −2 V vs Fc/Fc+), indicating that the CuII complexes are very stable in solution. This is supported by superoxide dismutase (SOD) and human serum challenge experiments as well as the biodistribution, which all show that the benzene-based ligand has the highest in vitro and in vivo stability and that this was expected on the basis of the macrocycle ring size and shape and the highest degree of preorganization. This ligand is easy to functionalize for a possible coupling to biological vector molecules and/or fluorescence markers for PET (positron emission tomography) and multimodal imaging (i.e., PET and optical imaging).